A Comparative Study on the Energy Demand of Turkey: Coal or Natural Gas. Issue 1 (March 2013) - Capik, Mehmet; Kolayli, Hasan; Yılmaz, Ali Osman
Energy demand which has increased rapidly is estimated to increase also in the future. Coal and natural gas would continue to have primary role in electricity generation and industry. Turkey's energy consumption has been growing faster than its production. Natural gas is the greatest source in the energy consumption with a share of 32%. Lignite coal is major domestic energy source of Turkey and its reserves are 12.4 billion tons. Since most of the lignite reserves are low in quality, they are used mostly in electricity generation. On the other hand, Turkey has very limited natural gas reserves. Aim of this article is to evaluate the energy demand of Turkey based on hard coal, lignite and natural gas. As a result of the study it was determined that 70% of the primary energy consumption is met by imported energy sources. This figure shows that Turkey's dependency on foreign energy will continue to increase in following years in parallel with its economic growth. Turkey should increase the use of domestic sources, since foreign dependence of country can be minimized.